Pemanfaatan Limbah Sekam Padi (Oryza sativa Linn.) sebagai Media Fermentasi untuk Produksi Enzim Selulase oleh Aspergillus niger - Eksa Adhwa Fadhilah; Peristiwati; Wahyu Surakusumah (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
This study aims to optimize the production of cellulase enzyme by the cellulolytic fungus Aspergillus niger using rice husk powder (Oryza sativa Linn.) as substrate. Cellulase enzymes have important roles in various industrial applications, including the bioconversion of lignocellulosic waste into high-value products such as bioethanol, pulp, paper, and animal feed. The utilization of rice husk as a substrate offers economic and environmental advantages due to its abundant availability, low cost, and ability to reduce the volume of agricultural waste. The research method used a quantitative experimental approach to evaluate the effect of fermentation parameters, such as pH, temperature, and incubation time, on enzyme production. A. niger isolates were developed on carboxymethylcellulose (CMC) media to ascertain their cellulolytic capacity, with measurements of biomass, pH, temperature, and enzyme activity. The results showed that the biomass of A. niger increased from hour 0 to hour 96 at pH 4.5 to 5.5, and temperature 29.5°C to 30.5°C. The optimum condition for enzyme production was found at pH 4.5 and temperature 30.5°C, with the highest enzyme activity reaching 0.736 U/mL. These findings suggest that optimization of cellulase enzyme production from rice husk not only improves enzyme production efficiency, but also contributes to more sustainable waste management.